1999
DOI: 10.1007/bf02561615
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the acute cytotoxicity of the erlanger silver catheter

Abstract: The Erlanger silver catheter consists of a new form of polyurethane, which contains finely dispersed metallic silver. The aim of this study was to establish the biocompatibility of this intravenous catheter by investigating the acute cytotoxicity of extracts from the Erlanger silver catheter on human fibroblasts and lymphocytes. Extracts of the Erlanger silver catheter were not cytotoxic for MRC-5 human fibroblasts nor for sensitized phytohemagglutinin (PHA)-stimulated human lymphocytes. The addition of silver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…In contrast, other authors reported about no cytotoxic effects of silver and its good biocompatibilty [11,[54][55][56][57]. These conflicting results probably can be explained by varying silver concentrations acting on different cell types.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In contrast, other authors reported about no cytotoxic effects of silver and its good biocompatibilty [11,[54][55][56][57]. These conflicting results probably can be explained by varying silver concentrations acting on different cell types.…”
Section: Discussionmentioning
confidence: 60%
“…Due to the oligodynamic effect, the silver release is comparatively low and has been evaluated in previous studies [13]. Therefore, elementary silver is regarded as low cytotoxic only [54,58]. In the current study the silver concentrations around the prosthesis and in the organs did not cause histological changes or functional deficits of the organs.…”
Section: Discussionmentioning
confidence: 77%
“…The first involves denaturation, the disulfide bonds of bacterial proteins, which are essential elements of bacterial structure, become disjointed due to the catalytic effect of silver ion. The second involves oxidization, ionized silver helps generate reactive oxygen in the air, which in turn attach around the cell prevents it from reproduction, and cause cell death [4,9,10]. Synthesized silver nanoparticles retain these properties of silver and are produced using various colloidal processes that involve surfactant-stabilization [11].…”
Section: Discussionmentioning
confidence: 99%
“…Silver is well tolerated and exhibits exceedingly low toxicity profile with excellent tissue tolerance. The cytotoxicity, the haemocompatibility and the thrombogenicity of catheters impregnated with silver has been determined and shows excellent results [12][13][14].…”
Section: Oligodynamic Activity Of Silvermentioning
confidence: 98%